ANALISIS YURIDIS INKONSISTENSI PUTUSAN MAHKAMAH KONSTITUSI TERHADAP PUTUSAN PENGUJIAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM BERDASARKAN PERSPEKTIF SISTEM KETATA NEGARAAN - NIM. A1011201164, TIGAS SUKMA SEGARA (Jurnal Fatwa Hukum, 2024)
Abstract  The inconsistent actions of the Constitutional Court Judges who actually overruled three previous decisions with the same constitutional issue have shown the existence of a conflict of interest which succeeded in intervening with the Constitutional Court Judges. The aim of this research is to find out why the Constitutional Court is inconsistent with its decision on material review of Law Number 7 of 2017 concerning General Elections regarding open legal policy. The method used in this research is descriptive normative law. The research results show that there was a lot of controversy in making Decision Number 90/PUU-XXI/2023. The Constitutional Court which received the withdrawn application and carried out a confirmation hearing which was not included in the Constitutional Court's procedural law. The inconsistency of the Constitutional Court judges who changed direction after Anwar Usman's entry into the discussion of RPK Decision Number 90/PUU-XXI/2023. So, it is in Anwar Usman's interest to successfully intervene with the Constitutional Court judge which ended up granting the petition in part and an ultra petita where the Constitutional corrected it by adding an alternative as a requirement for a candidate for President/Vice President. So, as a countermeasure to prevent decisions from Constitutional Court Judges that are more inclined towards interests outside the court and create blurred legal interpretations by Constitutional Court Judges, it is necessary to reaffirm the 1945 Constitution regarding external supervision of Constitutional Court Judges in order to strengthen the existence of the principle of checks and balances in the state. democracy, namely the Indonesian state.Kata kunci : Inconsistency of judges; MK judges; conflict of interest;code of ethic  Abstrak  Tindakan inkonsistensi Hakim MK yang mengesampingkan tiga putusan sebelumnya dengan isu konstitusional yang sama telah menunjukkan adanya konflik kepentingan yang berhasil mengintervensi Hakim MK. Tujuan dari penelitian ini adalah untuk mengetahui mengapa Mahkamah Konstitusi tidak konsisten terhadap putusan pengujian materiil Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum terkait dengan open legal policy. Metode yang digunakan dalam penelitian ini adalah hukum normatif yang bersifat deskriptif. Hasil penelitian menunjukkan bahwasannya terdapat banyak kontroversi dalam pengambilan Putusan Nomor 90/PUU-XXI/2023. MK yang menerima permohonan yang telah ditarik serta melaksanakan sidang konfirmasi yang tidak ada di dalam hukum acara MK. Inkonsistensi hakim MK yang berubah haluan pasca masuknya Anwar Usman dalam pembahasan RPK Putusan Nomor 90/PUU-XXI/2023. Sehingga, kepentingan Anwar Usman berhasil mengintervensi hakim MK yang berujung mengabulkan permohonan sebagian serta adanya ultra petita dimana MK justru memperbaikinya dengan menambahkan alternatif sebagai syarat calon Presiden/Wakil Presiden. Sehingga sebagai langkah penanggulangan agar tidak terjadi putusan Hakim Mahkamah Konstitusi yang lebih condong pada adanya kepentingan di luar pengadilan dan membuat kaburnya penafsiran hukum oleh Hakim MK diperlukan penegasan kembali dalam UUD 1945, mengenai pengawas eksternal dari Hakim MK guna memperkuat eksistensi prinsip checks and balances dalam negara demokrasi, yaitu negara Indonesia.Keywords: Inkonsistensi hakim; hakim MK; konflik kepentingan; kode etik